Una nota sui portali di Bonino di Giacomo in Dalmazia - Fisković, Igor (ASPICE HUNC OPUS MIRUM: Festschrift on the occasion of Nikola Jakšić’s 70th birthday, 2020)
In his paper the author emphasizes the building capabilities of Bonino di Giacomo (Bonino di Jacopo) by summarizing the extant knowledge and data about his activities in Korčula, Dubrovnik, Split and Šibenik from 1408 to 1428. Indeed, in Croatian historiography he is regarded as a capable sculptor, known for his work in distinguishable Gothic style. Moreover, in all of the publications regarding Dalmatian art, including lexicons, he is regularly classified as a ”sculptor” with recognizable Lombard characteristics, which is considered a novelty in this region. However, from an overview of the archival sources mentioning his name, as well as from the analysis of building works with monumental portals attributed to him, it can be noted that he was an experienced architect and a planner as well. This can be corroborated by newly detected similarities between the plans of the cathedrals in Korčula and Šibenik, as well as the assumption that he was participating in a series of building activities on the communal buildings in Split. Moreover, in Dubrovnik and Šibenik he is titled as ”protomagister ecclesiae S. Blasii” and ”primus magister ecclesiae nuove S. Jacobi”. All of these conclusions are supplemented with the new and improved results of the iconographic analysis, which is why this short study can be regarded as a starting point for the new and more complete elaboration of the problem of the integral opus of Bonino di Giacomo on the Croatian coast.